The black book - Pamuk, Orhan 1952-; Freely, Maureen 1952-. (New York Vintage International/Vintage Books, 2006)
Galip is a lawyer living in Istanbul. His wife, the detective-novel-loving Ruya, has disappeared. Could she have left him for her ex-husband, Celal, a popular newspaper columnist? But Celal,...
Keywords: Missing persons -- Fiction; False personation -- Fiction